Design and Simulation of the Operating Speed Regulation Algorithm of Plot Cabbage Seed Combine Harvester (JOURNAL OF ADVANCES IN AGRICULTURE, 2020)
Aiming at the problems of the single control scheme, the few aspects of monitoring and diagnosis, and the large delay time of the plot combine harvester, this paper designs the forward speed control algorithm of the plot Chinese cabbage seed harvester. This paper studies the theory of association rules, has used SQL Server to build a database including the job parameters of the main monitoring objects, and has mined the association rules between the job parameters and the feed amount through Analysis Service. Combining the knowledge of association rules and ordinary fuzzy PID algorithm, the article has built a model and performed simulation verification. The results show that the algorithm can adjust the forward speed reasonably and quickly when the feed volume increases.